2013
DOI: 10.1603/ec13216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bt Maize and Soil Insecticides on Yield, Injury, and Rootworm Survival: Implications for Resistance Management

Abstract: A 2-yr field experiment was conducted to determine the effects on Diabrotica spp. (Coleoptera: Chrysomelidae) of an insecticidal seed treatment (Poncho 1250, (AI) /clothianidin) and a granular insecticide (Aztec 2.1G, (AI)/tebupirimphos and cyfluthrin) alone and in combination with maize producing the insectidical toxin Cry3Bb1 derived from the bacterium Bacillus thuringiensis (Bt). Yields for Bt maize plots were significantly greater than for non-Bt maize; however, insecticides did not significantly affect yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 52 publications
3
40
4
Order By: Relevance
“…In most of the scenarios examined, application of soil insecticides to Bt-protected plants did not provide significant additional root protection except when NIS ratings exceeded 2.0 for the non-Bt treatments. These results are consistent with other published research on Cry3Bb1 susceptible populations (Petzold-Maxwell et al 2013, Estes et al 2015). In this high feeding pressure scenario, there was an improvement in root protection from the addition of a soil insecticide on Cry34Ab1/Cry35Ab1 single trait-protected plants.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In most of the scenarios examined, application of soil insecticides to Bt-protected plants did not provide significant additional root protection except when NIS ratings exceeded 2.0 for the non-Bt treatments. These results are consistent with other published research on Cry3Bb1 susceptible populations (Petzold-Maxwell et al 2013, Estes et al 2015). In this high feeding pressure scenario, there was an improvement in root protection from the addition of a soil insecticide on Cry34Ab1/Cry35Ab1 single trait-protected plants.…”
Section: Discussionsupporting
confidence: 94%
“…For additional root protection against the perceived threat, corn growers began to consider adding prophylactic soil insecticides to single trait and pyramided trait technologies. Petzold-Maxwell et al (2013) found few benefits from adding a soil insecticide to trait-protected corn when the crop is exposed to Bt-susceptible populations of corn rootworm. Tinsley et al (2016) found a significant trend where soil insecticides provided additional root protection in Bt-susceptible populations as compared to Bt single and pyramided traits; however, the magnitude of the difference indicated that even at high pressure, producers were unlikely to experience a positive economic return.…”
mentioning
confidence: 99%
“…In a field study with Cry3Bb1-resistant western corn rootworm, Gassmann (2012) documented a significant reduction in western corn rootworm adult emergence and root injury with the application of soil insecticide to Cry3Bb1 corn, whereas in a study of Cry3Bb1-susceptibe western corn rootworm, Petzold-Maxwell et al (2013a) found no effect of soil insecticide on root injury to Cry3Bb1 corn but significant reduction in adult emergence. In our study, the application of soil insecticide to Cry3Bb1 corn significantly reduced root injury by western corn rootworm; however, it did not reduce the adult emergence in problem fields (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…; Petzold‐Maxwell et al. ). Across field collections in experiment 1, the average total emergence period in the greenhouse was 33 days.…”
Section: Methodsmentioning
confidence: 99%